ACE2 receptor polymorphism in humans and animals increases the risk of the emergence of SARS-CoV-2 variants during repeated intra- and inter-species host-switching of the virus - Devaux, Christian A.; Fantini, Jacques (Frontiers in Microbiology, 2023)
Like other coronaviruses, SARS-CoV-2 has ability to spread through human-to-human transmission and to circulate from humans to animals and from animals to humans. A high frequency of SARS-CoV-2 mutations has been observed in the viruses isolated from both humans and animals, suggesting a genetic fitness under positive selection in both ecological niches. The most documented positive selection force driving SARS-CoV-2 mutations is the host-specific immune response. However, after electrostatic interactions with lipid rafts, the first contact between the virus and host proteins is the viral spike-cellular receptor binding. Therefore, it is likely that the first level of selection pressure impacting viral fitness relates to the virus's affinity for its receptor, the angiotensin I converting enzyme 2 (ACE2). Although sufficiently conserved in a huge number of species to support binding of the viral spike with enough affinity to initiate fusion, ACE2 is highly polymorphic both among species and within a species. Here, we provide evidence suggesting that when the viral spike-ACE2 receptor interaction is not optimal, due to host-switching, mutations can be selected to improve the affinity of the spike for the ACE2 expressed by the new host. Notably, SARS-CoV-2 is mutation-prone in the spike receptor binding domain (RBD), allowing a better fit for ACE2 orthologs in animals. It is possibly that this may also be true for rare human alleles of ACE2 when the virus is spreading to billions of people. In this study, we present evidence that human subjects expressing the rare E329G allele of ACE2 with higher allele frequencies in European populations exhibit a improved affinity for the SARS-CoV-2 spike N501Y variant of the virus. This may suggest that this viral N501Y variant emerged in the human population after SARS-CoV-2 had infected a human carrying the rare E329G allele of ACE2. In addition, this viral evolution could impact viral replication as well as the ability of the adaptive humoral response to control infection with RBD-specific neutralizing antibodies. In a shifting landscape, this ACE2-driven genetic drift of SARS-CoV-2 which we have named the 'boomerang effect', could complicate the challenge of preventing COVID with a SARS-CoV-2 spike-derived vaccine.